PERBANDINGAN MEDICATION ERROR PADA PERESEPAN ELEKTRONIK DAN PERESEPAN MANUAL PADA TAHAP PRESCRIBING DI APOTEK KOTA PALU - Alwiyah Mukaddas; Ingrid Faustine; Nofriyanti Nofriyanti (As-Syifaa Jurnal Farmasi, 2021)
Prescribing drugs is now growing, as evidenced by the existence of electronic prescribing that have been applied in several hospitals and pharmacies. The development of this prescribing method does not rule out the possibility of increasing the incidence of medication errors in prescribing. So, it is necessary to identify the prescribing that has been implemented, especially in drugstore at Palu City. The purpose of this study was to look at the comparison of medication errors at the prescribing stage which included aspects of prescribing completeness and therapeutic errors in electronic prescribing at Drugstore X and manual prescribing at Drugstore Y in Palu city in 2018. This type of research is a descriptive study with retrospective data collection. Samples taken in the form of secondary data are prescribing using purposive sampling method. The results obtained in this study are, the prevalence of medication error at the prescribing stage of electronic prescribing in drugstore at Palu City includes data, patient's body weight is 2%, doctor's license 100%, doctor's telephone number 100%, doctor's initial 100%, dosage form 97% and 90% strength of the drug. While the prevalence of medication error at the prescribing stage of manual prescribing in Drugstore Palu City is data, the patient's age is 2%, the patient's body weight is 99.1%, the patient's sex is 100%, the doctor's license is 91.6%, the doctor's telephone number is 80%, initial doctor 42.7%, 88% dosage form and 65% drug strength. Based on these results, it can be concluded that the use of electronic prescribing is better than manual prescribing.